Relationship between Securitisation and Residential Mortgage Market Yields in Malaysia: A Cointegration Approach - Mukaramah Harun; Yusuf Haji Othman (International Journal of Management Studies, 2007)
This article examines the possible long-run association between residential mortgage securitisation and yield spread for residential mortgage rates in the Malaysian primary markets. The cointegration and error-correction framework was applied to quarterly data from the third quarter of 1988 to the first quarter of 2003. Unit root tests revealed that each variable is non-stationary in levels at the 5 percent level of significance. The cointegration test shows a cointegration between these variables. The estimate of error-correction model shows a high adjustment speed for yield spread to the deviation in the longrun equilibrium. Meanwhile, securitisation responded very slowly to the deviation.